Viruses and Mycoplasma pneumoniae are the main etiological agents of community‐acquired pneumonia in hospitalized pediatric patients in Spain. Issue 1 (18th October 2021) - Otheo, Enrique; Rodríguez, Mario; Moraleda, Cinta; Domínguez‐Rodríguez, Sara; Martín, María D.; Herreros, María L.; Vázquez, Carmen; Folgueira, María D.; Pérez‐Rivilla, Alfredo; Jensen, Julia; López, Agustín; Berzosa, Arantxa; et al.
Abstract: Objectives: To describe the etiology of community‐acquired pneumonia (CAP) in hospitalized children in Spain and analyze the predictors of the etiology. Hypothesis: The different etiological groups of pediatric CAP are associated with different clinical, radiographic, and analytical data. Design: Observational, multicenter, and prospective study. Patient selection: This study included children aged 1 month to 17 years with CAP, who were hospitalized between April 2012 and May 2019. Methods: An extensive microbiological workup was performed. The clinical, radiographic, and analytical parameters were analyzed for three etiological groups. Results: Among the 495 children included, at least one causative pathogen was identified in 262 (52.9%): pathogenic viruses in 155/262 (59.2%); atypical bacteria (AB), mainly Mycoplasma pneumonia, in 84/262 (32.1%); and typical bacteria (TyB) in 40/262 (15.3%). Consolidation was observed in 89/138 (64.5%) patients with viral CAP, 74/84 (88.1%) with CAP caused by AB, and 40/40 (100%) with CAP caused by TyB. Para‐pneumonic pleural effusion (PPE) was observed in 112/495 (22.6%) patients, of which 61/112 (54.5%) presented a likely causative pathogen: viruses in 12/61 (19.7%); AB in 23/61 (37.7%); and TyB in 26/61 (42.6%). Viral etiology was significantly frequent in young patients and in those with low oxygen saturation, wheezing, no consolidation, and high lymphocyte counts. CAP patients with AB as the etiological agent had a significantly longer and less serious course as compared to those with other causative pathogens. Conclusions: Viruses and M. pneumoniae are the main causes of pediatric CAP in Spain. Wheezing, young age, and no consolidation on radiographs are indicative of viral etiology. Viruses and AB can also cause PPE. Since only a few cases can be directly attributed to TyB, the indications for antibiotics must be carefully considered in each patient.